Tatanan Hirarki Gereja yang Apostolik dalam 1 Klemens - Febrianto, Paulus (Lux et Sal, 2023)
The apostolicity of the Church is the continuation of Christ's mandate, who from the beginning established the apostles as the successors of His work of salvation in the world. The continuity of the office of apostle becomes Tradition that is preserved as an expression of uninterrupted shepherding. Since the Ancient Church, the Church's hierarchical order has developed to take on a stable form so that today the ordained carry out their mission to serve the people of God. The First Letter of Clement is one of the earliest evidences after the era of the apostles that emphasizes the important role of the community leader who is chosen and appointed specifically in their function and role as part of the members of the Body of Christ.